The Medical and Psychological Effect of Hate Crimes and Hate Speech on Vulnerable Social Groups (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study would be analyzing and interpreting the intricacies of hate speech in two-fold. Firstly, theauthors would be meticulously analyzing the legal parlance of the term ‘hate speech’ in the present aeon andits repercussions, i.e., outline the constitutive and consequential harm faced by the people that goes beyondlegal texts and judgments and beyond the legal notion of hate speech.In furtherance, this research article would address the aftereffects of hate speech medically and how it takesa psychological toll on minority bigotry and pervasive gender or ethnic differences by using a plethora ofwell-known logical research approaches that are unique to analytic philosophy.Hate speech cases have resulted in bans on campus, legal rulings, and national controversy. The term ‘FreeSpeech’ and ‘Hate Speech’ has been misconstrued and used misappropriately. The prime reason is theabsence of precise clarification and the unbelievably wide usage of the term. The targeted communitiesexperiencing hate speech are of paramount importance but are often overlooked due to the legitimacy oflaws pertaining to hate speech.